A study on participation as individual empowerment in Malaysian welfare reform - Jaganathan, Jayamalar; Abu Samah, Asnarulkhadi (International Organization Of Scientific Research, 2015)
Participation in productive welfare programmes, a social innovation for welfare reform in Malaysia, provided opportunities to welfare recipients for individual empowerment and financial sustainability without depending on welfare aid. The challenges for the government however, lies in sustaining the interest level of welfare recipients to ensure effective and continued participation in the productive welfare programmes which is a form of self-employment for financial stability and self-sufficiency. Hence, this study aims at measuring the perceived attributes based on Roger’s Model of Diffusion of Innovation (DOI) namely, relative advantage, compatibility, complexity, observability and trialability of productive welfare and its effect on participation and the empowerment outcomes of the programme participants This quantitative study was carried out among 266 productive welfare participants selected non-randomly from 11 districts in Selangor and findings were supported by informal interview with these respondents. The relationships between variables and the contribution of the five dimensions of perceived attributes that influenced participation as well as the economic and psychological empowerment outcomes among the participants was analysed using SPSS (Version 20.0) for descriptive statistics and AMOS Structural Equation Model (SEM AMOS 18). The Pearson correlation analysis result shows that all the five perceived attributes had a significant positive and high relationship with participation and empowerment outcomes with trialability being a significant predictor of psychological empowerment, while compatibility, trialability and participation were unique predictors for economic empowerment.